Komunikasi Bencana BPBD Klaten dalam Mitigasi Erupsi Gunung Api Merapi di Tegalmulyo, Kemalang, Klaten - Jamaluddin Asrofi; Niken Puspitasari (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2022)
One of the potential disasters in Indonesia that is of concern is a volcanic eruption. Indonesia is recorded to have approximately 127 active volcanoes, one of which is Mount Merapi. The role of disaster communication is quite important in mitigation efforts to reduce the impact of a disaster. Several problems related to communication often occur during a disaster emergency, including incomplete information conveyed which causes confusion, interrupted communication, and confusion due to coordination failure. BPBD Klaten Regency has a quite strategic role as an implementer related to disaster in Klaten Regency, in this case the Merapi Volcano Eruption. This study aims to analyze disaster communication carried out by BPBD Klaten Regency in an effort to mitigate the eruption of Merapi Volcano in Tegalmulyo Village. This study uses a qualitative method. Data collection is done by way of interviews, observation and documentation. The subjects in this study were the BPBD of Klaten Regency. The results of this study indicate that the BPBD of Klaten Regency has carried out several programs related to efforts to deal with the Mount Merapi Eruption disaster in Tegalmulyo Village. Some of these efforts include conducting outreach, training, and forming the Dashing Disaster Village and the Brotherhood Village. In addition, the BPBD of Klaten Regency is also trying to open up information and collaborate with the media to publish informationKeywords: Disaster Communication, Mitigation, Merapi Eruption, BPBD Klaten Regency